2016
DOI: 10.32890/mjli2016.13.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Teacher Leadership Competency Scale

Abstract: Purpose-The main purpose of the study was to develop an empirically validated Teacher Leadership Competency Model (TLCM) which would enhance teacher leadership competencies in Malaysian secondary schools. There is currently no established instrument that measures teacher leadership competency, particularly in the Malaysian context. Methodology-Structural equation modeling (SEM) utilizing AMOS Version 22 was employed to develop the model. Exploratory factor analysis was utilized to identify the underlying facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In an attempt to determine why educators use Instagram, Carpenter (2020) revealed that most educators used the social networking platforms to share ideas and affirmation, with a subset of users monetizing some of the idea exchanges. On this note, we will examine the teacher leadership competency model (TLCM) updated by Yuet, Yusof and Mohamad (2016) through the lens of collaboration and networking on social media. The TLCM was constructed built on the basis of four types of models (Kho, Hamidah & Syed, 2015).…”
Section: Awareness Of Potential Returns On Investmentsmentioning
confidence: 99%
“…In an attempt to determine why educators use Instagram, Carpenter (2020) revealed that most educators used the social networking platforms to share ideas and affirmation, with a subset of users monetizing some of the idea exchanges. On this note, we will examine the teacher leadership competency model (TLCM) updated by Yuet, Yusof and Mohamad (2016) through the lens of collaboration and networking on social media. The TLCM was constructed built on the basis of four types of models (Kho, Hamidah & Syed, 2015).…”
Section: Awareness Of Potential Returns On Investmentsmentioning
confidence: 99%
“…Learners at the age of four to six portray high imaginative and creative thinking skills which require the needs for preschool teachers to actively interact and practice fun innovative inquiry in virtual and physical learning environments. Referring to various fun innovative inquiry materials would enhance preschool teachers' peer leadership competency in leading their peers towards mobilizing effective fun innovative inquiry in the world full of volatility, uncertainty, complexity and ambiguity (Yuet, Yusof & Syed Mohamad, 2016). Identifying critical and creative thinking skills, attributes, best practices, as well as cultures for nurturing innovation contribute to innovative capability of individuals and organizations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, self-directed leadership competency would enhance preschool teachers' professionalism as peer leaders (Fanny & Mansor, 2019). Likewise, 'Fly with v-PeLFII Model' was developed to enhance peer leadership and innovative capability of individual preschool teachers in conducting fun innovative inquiry through virtual and nonvirtual interaction platforms (Yuet, Yusof & Syed Mohamad, 2016). Congruently, leading preschool teachers in practicing industrial revolution 4.0 technologies provides advantages for paradigm shift in instructional practices (Gerekli et al, 2021;Ghouri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%